(untitled) (Вісник: Міжнародні відносини, 2025)
Background. The purpose of this article is to describe the role of inflation in world politics as an objective way of assessing the position of the hegemon by other participants in the international process. To do this, we will first organize the broad context of political reality on the basis of the theory of hegemonic stability, then briefly describe its white spots and ways to solve them, and then, based on the method from abstract to concrete, we will proceed to describe the problems of inflation for states that claim high status. Next, we will pay special attention to the analysis of the inflation factor for the American hegemon. For this, we will use materials of a social, historical and political and economic nature. Methods. In the research process, analytical, sociological, abstract-to-concrete, comparative, systemic, functional and historical methods were used. Results. The 2020 epidemic sharply intensified inflationary processes, as not all economies opened at the same time after quarantine, which complicated global supply chains, while the increase in debt levels to maximum values caused irreversible damage to future growth prospects. In essence, in modern conditions, inflation begins to work as a mechanism that allows arbitrarily and unfairly taking from some, while giving to others, which increases domestic political polarization. The emergence of revisionists like B. Sanders or D. Trump in the electoral field, who remove globalists from power through elections, can be seen as evidence confirming this theory. Conclusions. As a conclusion, it is noted that inflation interferes with trust, and also destroys the society of the hegemonic country, which, therefore, incurs high costs in maintaining global stability. Inflation against the hegemon does not act directly, but contributes to an indirect limitation of opportunities. Although it is possible to live with high inflation for years - even decades - inflation can, however, lead to a highly unequal society that will begin to bring isolationist politicians to power, but in conditions of uncontrolled inflation, military budgets are reduced and make it difficult to fulfill political obligations to finance military activities, purchase new weapons and support military personnel.